Oral Health Knowledge, Attitudes, and Behaviors (KAB) of German Dental Students: Descriptive Cross-Sectional Study - Riad, Abanoub; Buchbender, Mayte; Howaldt, Hans-Peter; Klugar, Miloslav; Krsek, Martin; Attia, Sameh (Frontiers in Medicine, 2022)
Germany's 2030–oral health agenda incorporates behavioural targets such as twice-daily toothbrushing and routine dental check-ups. Given the professional and social roles of dentists in oral health promotion, the oral health-related knowledge, attitudes, and behaviours (KAB) of dentists and dental students became worth investigation. The present study was designed as a descriptive cross-sectional study that aimed to evaluate oral health KAB of German dental students using the Hiroshima University – Dental Behavioural Inventory (HU-DBI). A total of 508 dental students filled in the questionnaire, out of which 74.2% were females, 38.8% were clinical students, 11.4% reported tobacco smoking at least once a week, 26.6% reported drinking alcohol at least once a week, and 82.9% reported suffering from problematic internet use. The overall HU-DBI score was high (7.67 ± 1.32), and it was slightly higher among females (7.70 ± 1.33) than males (7.59 ± 1.29), and gender-diverse students (7.33 ± 1.37). Clinical students (7.88 ± 1.26) had a significantly higher HU-DBI score, especially in the domain of oral health behaviours, compared with preclinical students (7.53 ± 1.34). A significant improvement in oral health behaviours and HU-DBI score was found between the third- vs. the fourth year, which corresponds to the period when prophylaxis, hygiene, and periodontology courses are delivered. Tobacco smoking was significantly associated with poor oral health knowledge, behaviours, and overall HU-DBI score. Problematic internet use and alcohol drinking had slightly lower HU-DBI scores. The findings of the present study call for early implementation of preventive dentistry elements in German curricula and addressing oral health needs of gender minorities in Germany by future epidemiologic studies.